Effects of Zinc chloride concentration and thermal annealing on the growth of zinc sulfide nanostructures - Rivera, Rolen Brian P.; Alguno, Arnold C. (2015)
Zinc sulphide (ZnS) nanostructures were grown using chemical bath deposition technique. Scanning electron microscopy-energy dispersive xray was used to characterize the surface morphology and composition; ultraviolet visible spectroscopy was used to approximate the band gap energy and nanostructures. Using these techniques, we have specified the effects of ZnCl2 concentration while thermal annealing triggers an increase in nanostructures size. The band gap energy decreased with increasing thermal annealing temperature. ZnCl2 concentration and thermal annealing greatly affected the morphological, optical and electrical properties of ZnS nanostructures.
Keywords: Nanostructured materials